Handbook of flame retardants - Wypych, George (ChemTec Publishing, 2021)
"Handbook of Flame Retardants contains an extensive evaluation of existing literature, products, and patents on subjects related to flame retardance. Two separate publications are simultaneously released on this critical subject, each complementing each other: Databook of Flame Retardants and Handbook of Flame Retardants. The Databook contains information and data of over 350 commercial and literature-based products, and Handbook explains their roles, selection, mechanism of action, and use in different polymers and products. From information included in Introduction, it can be inferred that global market of flame retardant is large and growing. Also, high fluidity is observed in permitted applications of various groups of flame retardants, mainly because of increased public awareness and scrutiny, but also because of the large time lag between the implementation of new groups of flame retardants and the flow of negative observations, which frequently lead to their replacement."-- Provided by publisher.
Keywords: Fireproofing agents -- Handbooks, manuals, etc.; elektronické knihy; electronic books